Pengaruh Model Problem-Based Learning Berbantuan Permainan Monopoli terhadap Hasil Belajar Siswa Sekolah Dasar pada Materi Keberagaman Budaya - Novita, Catrin Erma; Prasetyaningtyas, Fitria Dwi (Department of Primary School Teacher Education, Faculty of Teacher Training and Education, Jambi University, 2025)
This study was motivated by the low learning outcomes of fourth-grade elementary school students, which were still below the (KKTP). This condition was caused by teachers still using old learning models and media and not yet implementing innovative learning models and media, resulting in learning becoming less interesting and causing boredom among students. This study aims to analyse the effect of implementing the (PBL) model assisted by an educational monopoly game on cultural diversity on student learning outcomes in IPAS learning. This study uses a quantitative approach with an experimental research type and a quasi-experimental design. The research sample consisted of 56 students, with class IVB designated as the experimental class and class IVA designated as the control class. Data collection techniques in this study were carried out through observation, interviews, documentation, and testing. Learning outcome data were analysed using the t-test (independent sample t-test). The results of the analysis showed that tcount > ttable (5.605 > 2.004) with a significance value (0.000 < 0.05), so Ho was rejected and Ha was accepted. It can be concluded that the application of the PBL model supported by media monopoly with cultural diversity has a significant effect on student learning outcomes.